Before tomorrow Le jour avant le lendemain - Cousineau, Marie-Hélène; Ivalu, Madeline (Alliance Vivafilm, 2009)
D'après le roman de Jørn Riel. Deux familles inuites se rencontrent pour une fête estivale. La nourriture est abondante et l'avenir semble prometteur, mais Ningiuq, une vieille femme forte et sage, ne cesse de s'inquiéter. Elle voit son monde comme fragile et le traverse avec un sentiment d'effroi omniprésent. Ningiuq part avec son petit-fils vers une île isolée, où ils sèchent les prises et les stockent pour l'hiver. La tâche est terminée et la saison chaude touche à sa fin, car ils attendent en vain que les autres viennent les chercher.
Keywords: 1800-1899; amériques; canada; cinéma; communication; cours; discipline; fem3200; histoire et politique; inuits; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
https://nhfpl.kanopy.com/node/4694913
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis